Effect of transactional analysis intervention on parent-adolescent conflict and emotional regulation among adolescents in Bangladesh - Tanni, Khandaker Tasmina; Zainudin, Zaida Nor; Hassan, Siti Aishah; Yusop, Yusni Mohammad; Asri, Alia Sarah (Universiti Putra Malaysia, 2024)
Transactional Analysis (TA) focuses on the paradigm of the parent, adult, and child ego states. TA therapy tools have successfully reduced conflicts between parents and adolescents, emotional regulation, and depression. The main objective of this study is to examine the effect of transactional analysis intervention on parent-adolescent conflict and emotional regulation. This research uses pre-test, post-test control and experimental group design. The subjects were 60 students randomly allocated to one of two groups: experimental (TA Intervention) or control (non-TA Intervention). The descriptive analysis described the participants’ demographic profile, including age, gender, education grade, and parental marital status. The independent sample t-test evaluated the mean scores of parent-adolescent conflict, emotional regulation, and depression between the experimental and control groups’ post-test findings. The MANOVA determined the considerable effect of groups and genders on Parent-adolescent conflict, emotional regulation, and depression. The findings demonstrated that Transactional Analysis was more successful for adolescents dealing with parent-adolescent conflict, emotional regulation, and depression in the experimental group than in the control group. The current study is a pioneer experimental investigation in Bangladesh to determine the effect of TA on parent-adolescent conflict, emotional control, and depression, which will assist mental health professionals in better treating adolescent conflict, emotional regulatory strategies, and depression in Bangladeshi adolescents.